Pouch Use Among Infants Does Not Impact Exposure to Other Forms of Fruits and Vegetables: Data from the Feeding Infants and Toddlers Study (FITS) 2016. (29th May 2020) - Finn, Kristen; Lenighan, Yvonne; Eldridge, Alison; Kineman, Brian; Pac, Susan
Abstract: Objectives: Baby food pouches have grown in popularity along with concerns about their impact on oral motor development. These concerns assume that baby food pouches are a primary food source and that they limit exposure to fruits and vegetables in other forms. The purpose of this study is to determine how often infants from the Feeding Infants and Toddlers Study (FITS) 2016 used pouches and if those who used pouches were as likely to also consume other forms of fruits and vegetables as those who did not. Methods: FITS is the largest nationally representative cross-sectional dietary survey of caregivers of children aged 0–47.9 months in the U.S. For this analysis, a questionnaire and 24-hour dietary recall were used to assess pouch use and fruit and vegetable intake among children aged 6–11.9 months ( n = 989). A "pouch user" was a child receiving a pouch at least once per week per the questionnaire. All others were categorized as "non-users." In the 24-hour recall, fruits and vegetables were categorized as "baby food" if it was a commercial or homemade pureed fruit or vegetable or "non-baby food" if it was any other form of fruit or vegetable. Descriptive statistics were tabulated for frequency of pouch use and % of pouch users and non-users who consumed baby food and non-baby food fruits and vegetables. Results: Per the questionnaire, 36% of 6–11.9 month olds were pouch users ( n = 314) and 64% were non-users ( n = 675). Among pouch users, 6% received food from a pouch daily ( n = 51), and 5% received food from a pouch more than once per day ( n = 40). Per the 24 hour recall, the percentages of pouch users and non-users who consumed baby food fruits (54.3% vs. 50.4%) and vegetables (45% vs. 43.3%) in any packaging were similar. More pouch users consumed non-baby food fruits and vegetables compared to non-users (54.3% vs. 36.5% and 49.2% vs. 37.4%, respectively). Conclusions: Roughly a third of infants are pouch users, but daily use is not common. Pouch users consume non-baby food fruits and vegetables as often as non-users. These findings indicate that infants who are exposed to baby food pouches are also exposed to other forms of fruits and vegetables, so the impact of food pouches on oral motor development in infants may be limited. Funding Sources: FITS 2016 and this analysis were funded by Nestlé Research, Vers-chez-les-Blanc, Lausanne, Switzerland.